Particulele afirmative în limba română – perspectivă diacronică și areală - Klimkowski, Tomasz (Studia Romanica Posnaniensia, 2020)
The present article analyses the Romanian affirmative particles from a diachronic and areal perspective in order to determine their origin. The analysis of a corpus of original literary texts and translations of religious texts as well as dictionaries and grammars from different epochs has resulted in distinguishing in Romanian the following affirmative particles: aşa (since the 16th, and especially the 17th century), ei (in the 16th century), ie (since the second half of the 18th century) and da (since the 19th century). As the last three can be put in the East European areal context, a natural explanation of their origin would be the assumption that they were borrowed respectively from Church Slavonic, German and Slavic. However, also because of the special status of affirmative particles as a part of basic vocabulary of most languages, we propose to apply to them the foothold theory inspired by Abraham’s half-open doors theory (2011). Accordingly, we believe that borrowing the particle ei from Church Slavonic could have used as a foothold the Old Romanian conjunction e (< lat. et) and the ie borrowed from German was superposed on the Romanian verbal form e ‘is’. On the other hand, the Slavic loanword da coincided with the inner semantic evolution of the Romanian forms dară dar da from an adversative conjunction to an affirmative particle.